A Predictive Correlation for Dynamic Viscosity of Fatty Acid Methyl Esters and Biodiesel. (5th June 2019) - Roosta, Aliakbar; Bardool, Roghayeh
Abstract: The viscosity of biodiesel, which is a mixture of fatty acid methyl esters (FAME), is an important physical property in the injection and efficient combustion. In this study, a simple correlation, with only one adjustable parameter, is proposed for predicting the viscosity of FAME and their mixtures (biodiesel) as a function of temperature. First, the adjustable parameter of the correlation is calculated for various FAME. The average absolute relative deviation (AARD) is obtained to be 0.97% for 226 data points. Second, the adjustable parameter of FAME is connected to the number of carbon atoms and the number of double bonds to build a predictive correlation for the calculation of viscosity. The AARD for 226 data points is obtained to be 2.28%. Third, the proposed model is employed to predict the viscosity of biodiesel without introducing any new adjustable parameter. To predict the viscosity of biodiesel, the average of the adjustable parameter is applied to the correlation. The AARD of 2.96% is obtained for 185 data points comprised of 23 different biodiesels. To better understand the ability of the correlation in the estimation of the viscosity of biodiesel and FAME, a comparison is made between the present correlation and a number of correlations available in the literature.